1996
DOI: 10.1046/j.1464-410x.1996.23024.x
|View full text |Cite
|
Sign up to set email alerts
|

Burns to the genitals and the perineum in children

Abstract: Objective To determine the management of perineal and genital burns in children. Patients and methods Twenty‐seven children (aged 6 months to 12 years) suffering from genital or perineal burns between 1981 and 1995 were reviewed. Most burns occurred in boys (70%), were due to scalds (85%) and caused superficial second‐degree lesions (63%). The initial treatment consisted of topical antimicrobials or grafting with allografts. Results Spontaneous healing by conservative therapy, not early excision therapy, occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Weiler-Mithoff et al [6] reported an unusual case of burn injury to the genital area by fireworks in a suicide attempt. Michielsen et al [7] reported burn injury by hot fluid (55%), flame (24%), and chemicals (16%) in a study of 4,216 patients, while scalds were responsible for 85% burns in a review of 27 cases by the same authors. [8] Quayle et al [9] found increased burn injury rates in African-American girls (0–4 years of age) in counties with a high poverty rate in Missouri (USA).…”
Section: Discussionmentioning
confidence: 99%
“…Weiler-Mithoff et al [6] reported an unusual case of burn injury to the genital area by fireworks in a suicide attempt. Michielsen et al [7] reported burn injury by hot fluid (55%), flame (24%), and chemicals (16%) in a study of 4,216 patients, while scalds were responsible for 85% burns in a review of 27 cases by the same authors. [8] Quayle et al [9] found increased burn injury rates in African-American girls (0–4 years of age) in counties with a high poverty rate in Missouri (USA).…”
Section: Discussionmentioning
confidence: 99%
“…Topical antimicrobials have been recommended as conservative management of external genital and perineal burns. 5 Huppert et al 4 managed their case of a 13-year-old with 42 hours exposure to 7 alkaline batteries causing third-degree burns with intravenous antibiotics, intravaginal estrogen cream and an oral nonsteroidal anti-inflammatory. Follow-up was intense with repeat examination under anesthesia at 5 days and weekly for 7 weeks to exclude delayed injury such as stricture, fistula, or perforation.…”
Section: Discussionmentioning
confidence: 99%
“…More burns by spoiled hot beverages and boiling water are reported when there are more children in the study population. Two reports deal with burn injuries in children solely 4,6 . Angel et al .…”
Section: Causes Of Genital Burnsmentioning
confidence: 99%
“…Michielsen et al . reported an 85.1% incidence in the Academic Surgical Centre Stuivenberg of Antwerp, Belgium 6 . Most chemical burns are contact injuries.…”
Section: Causes Of Genital Burnsmentioning
confidence: 99%